If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-161=7(5-4n)
We move all terms to the left:
-161-(7(5-4n))=0
We add all the numbers together, and all the variables
-(7(-4n+5))-161=0
We calculate terms in parentheses: -(7(-4n+5)), so:We get rid of parentheses
7(-4n+5)
We multiply parentheses
-28n+35
Back to the equation:
-(-28n+35)
28n-35-161=0
We add all the numbers together, and all the variables
28n-196=0
We move all terms containing n to the left, all other terms to the right
28n=196
n=196/28
n=7
| 3^2w^2-8^2=0 | | 4(×-2)=2(x-4)+2× | | 6k=19.8 | | 10x-4-2x=x+10 | | 7y-2y=24 | | 12=z/6-30 | | 40(4y-9)=5y | | 5(m+4)=-2(-4-m)+30 | | 3c–14=19 | | 4(3x+2)=-10 | | -v/5=6.4 | | n-16(-2)=-24 | | 2/3x+15=-5 | | a+1=15 | | 7w+21=91 | | h-4=h+9 | | x=-10000+Y | | 9t=–7+8t | | 6m+10=1m | | 3x+4=x+18= | | 6(2+k)-5=7 | | 4(2x−5)=−3(5−x) | | -11.77=d/4-15.77 | | -j/9=-8 | | n/7-12=5n+5= | | 5(2x-7)-4x=19 | | 13x+3=3x51 | | 2z+62=180 | | 5x–8+2x=7x–8 | | −6(−3y−6)−10=(6y−8) | | y-6+3(3y+6)=-2(y+1) | | 6.5=r/3 |